Adolescent girls' experiences of menstruation and schooling in monastic schools in Magway Region, Myanmar: A mixed-methods exploration - Swe, Zay Yar; Mon, Nwe Oo; Than, Kyu Kyu; Azzopardi, Peter S.; Kennedy, Elissa C.; Davis, Jessica; Burns, Lia J.; Hennegan, Julie (Frontiers in Reproductive Health, 2022)
Background. Despite increasing recognition that menstruation matters for adolescent girls’ health and education, few studies have investigated menstrual health challenges and impacts in Myanmar. In this study we aimed to (1) understand the menstrual experiences of girls attending monastic schools in Magway Region, Myanmar and (2) explore the associations between their reported unmet menstrual health needs and school absenteeism. Methods. We undertook a mixed-methods exploration across 16 Monastic schools in rural and semi-rural areas. In-depth interviews with 10 adolescent girls, 10 Focus-Group Discussions (FGDs) with girls, 10 FGDs with boys, 5 FGDs with mothers, along with 24 key-informant interviews were analyzed using a framework approach to explore girls’ menstrual experiences and challenges in school settings. A cross-sectional survey of 421 post menarche girls (mean-age-14 years) was used to describe the prevalence of menstrual health challenges and test associations with self-reported school absenteeism. Results. Girls described a range of menstrual health challenges including access to information and social support, behavioural restrictions, stigma surrounding menstruation, difficulties managing menstrual bleeding and pain. Girls also described fear and distress associated with menstruation and impacts on school attendance and participation. Of girls surveyed, 12.8% had missed school due to their last period. In multivariable analysis, grade level (aOR=0.76 95%CI 0.60-0.97), menstrual pain (aOR=2.10 95%CI 1.10-4.00) and heavy bleeding (aOR=3.33 95%CI 1.51-7.34) were associated with absenteeism. Knowledge about menstrual biology was not related to absenteeism, but a more negative attitude towards menstruation may have predicted greater absences (aOR 1.34 95%CI 0.99-1.80). Confidence to talk to friends or teachers about menstruation was not associated with absenteeism, nor was using a disposable-pad or feeling confident to manage menses at school. However, feeling confident to ask a teacher for a pad was associated with greater absenteeism and may have indicated that girls more regularly needing to request products had lower attendance (aOR=1.93 95%CI 1.06-3.54). Conclusions. We found that girls in Magway Region face a range of menstrual health challenges impacting their education and wellbeing. Comprehensive programs that address informational and psychosocial needs, attitudes and norms surrounding menstruation, healthcare and physical resources should be developed and evaluated for this setting.